Analysis of the Legionella pneumophila fliI gene: intracellular growth of a defined mutant defective for flagellum biosynthesis. - Merriam, J J (1997)
Using a PCR-based strategy and degenerate oligonucleotides, we isolated a Legionella pneumophila gene that showed high sequence similarity to members of the fliI gene family. An insertion mutation that disrupted the fliI open reading frame was recombined onto the L. pneumophila chromosome and analyzed for its effects on production of flagella and intracellular growth. The mutation resulted in loss of surface-localized flagellin protein but had no effect on the ability of the bacteria to grow within cultured cells. Therefore, in spite of the fact that some aflagellar mutations render L. pneumophila unable to grow within macrophages, the isolation of this defined mutant confirms that production of flagella is not required for intracellular growth.